2018
DOI: 10.1021/acsami.8b16049
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Fluorine and Nitrogen as Anionic Dopants in Nickel-Rich Cathode Materials for Lithium-Ion Batteries

Abstract: Advanced lithium-ion batteries are of great interest for consumer electronics and electric vehicle applications; however, they still suffer from drawbacks stemming from cathode active material limitations (e.g., insufficient capacities and capacity fading). One approach for alleviating such limitations and stabilizing the active material structure may be anion doping. In this work, fluorine and nitrogen are investigated as potential dopants in Li1.02(Ni0.8Co0.1Mn0.1)0.98O2 (NCM) as a prototypical nickel-rich c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 62 publications
4
38
0
1
Order By: Relevance
“…To prove the chemical composition of CAMs containing lithium and transition‐metal ions, those were determined by inductively coupled plasma (ICP), inductively coupled plasma optical emission spectrometry (ICP‐OES), and atomic absorption spectroscopy (AAS) measurements. The additional presence of fluoride in the fluorinated CAMs was confirmed by IC,, ICP‐MS, ICP‐OES, electron microprobe, distillation‐thorium nitrate titration volumetric method, and F‐ion selective electrode measurements, but also ICP titration and microprobe …”
Section: Oxygen/fluoride Substitution and Elemental Analyticsmentioning
confidence: 84%
See 1 more Smart Citation
“…To prove the chemical composition of CAMs containing lithium and transition‐metal ions, those were determined by inductively coupled plasma (ICP), inductively coupled plasma optical emission spectrometry (ICP‐OES), and atomic absorption spectroscopy (AAS) measurements. The additional presence of fluoride in the fluorinated CAMs was confirmed by IC,, ICP‐MS, ICP‐OES, electron microprobe, distillation‐thorium nitrate titration volumetric method, and F‐ion selective electrode measurements, but also ICP titration and microprobe …”
Section: Oxygen/fluoride Substitution and Elemental Analyticsmentioning
confidence: 84%
“…For all CAMs described herein, the pXRD diffraction patterns of the synthesized samples could be indexed based on the α‐NaFeO 2 ‐type structure (R3m ) . It was observed that surface modification using the F‐sources: [NH 4 ]FHF, [NH 4 ]F, LiF, PTFE, PVDF, Li[PF 6 ], NaF, and F 2 did not alter the crystal structure and/or produce other secondary phases in the main layered structure of the pristine materials. Other authors reported an impurity of the material by the fluorination of the NCM CAMs, using LiF and NiF 2 as a F‐sources.…”
Section: Structural Characterizations With X‐ray Diffraction Vibratimentioning
confidence: 95%
“…Aside from cations doping, doping anions is another approach to modify the electrode materials. [ 94 ] Zhou et al investigated halogen instead of oxygen of LiCoO 2 by means of DFT calculations. [ 95 ] Results show that the halogen species enlarge the lithium slabs, which improves the lithium storage capacity, increases the lithium diffusion, and decreases the lattice and volume change during the (de)lithiation process.…”
Section: Modificationsmentioning
confidence: 99%
“…Figure 1 shows the processing of high nickel NCM ternary cathode material, which is due to cation mixed discharge caused by structural changes (Wang et al, 2017 ). Many studies believe that heterogeneous ions can be inserted into the lattice through doping, thereby changing the bond energy and lattice parameters and suppressing the deterioration of the internal structure of the lattice (Binder et al, 2018 ; Yu et al, 2020 ).…”
Section: Study On the Surface And Interface Structure Of High-nickel mentioning
confidence: 99%